TREATMENT OF CUTANEOUS LEISHMANIASIS WITH METHANOL EXTRACT OF ALLIUM SATIVA (GARLIC), AZADIRACHTA INDICA (NEEM) AND ACCACIA NILOTICA (GARAD) IN GEZIRA CENTRAL OF SUDAN - Khalid, F.A.; M.Abdalla, N.; Mohamed, H.O.; M.Toum, Abdalla; Almagzoib, Mobarak M.A.; Ali, M.Sedig (Gezira Journal of Health Sciences, 2006)
Objective: To assess the in vivo treatment of cutaneous leishmaniasis using certain medicinal agents and non medicinal agents in Gezira State, Sudan.  To evaluate the in vivo anti-lesihmanial activity of certain plant extracts that used traditionally in Sudan (Azadirachta indica (neem), Accacia nilotica (garad), Allium sativa (garlic, Thoum)). Methodology: A total of 72cases with cutaneous leishmanisis were studied in Wad Madani Dermatology Teaching Hospital (September 1999 - December 2000). They were from different parts of the Gezira state.    The patients were interviewed and examined followed a special designed questionnaire .The cases showed different types of lesions with different duration and appeared in different areas of the body.  The cases divided equally into six main groups (12 for each) for treatment with different agents including medicinal agents and plant methanol extracts.                       Results:  All cases showed good response (90.3%).The medicinal agents to plant methanol extracts response ratio was 1.0: 1. 03. Garlic had a 100% response it showed no significant difference with pentostam (control) ( P= 0.75). Also Neem showed no significant with pentostam (p= 0.09). Leishmanol and garad showed significant differences with the control (p= 0.05 & 0.04 respectively). Conclusion: According to the results we conclude that garlic and neem methanol extract have a good potential activity on leishmania parasite compaired to other studied agents